2018
DOI: 10.3389/fvets.2018.00195
|View full text |Cite
|
Sign up to set email alerts
|

Two Multicenter Surveys on Equine Back-Pain 10 Years a Part

Abstract: Despite back-pain being a common cause of poor performance in sport horses, a tailored diagnostic workflow and a consolidated therapeutic approach are currently lacking in equine medicine. The aim of the study was to assess the evolution in the veterinarian approach to diagnose and treat back-pain over a 10 years period. To investigate this topic, two surveys were addressed to equine veterinarians working in practice throughout Europe 10 years apart (2006 and 2016). The answers were organized in an Excel datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 49 publications
2
43
0
2
Order By: Relevance
“…Few horses in the study population were reported to have pain on palpation of the dorsum. Hyperalgesia of the dorsum has been described as a clinical sign of thoracolumbar pain in the horse and has been documented in one report describing a study with experimentally induced pain of the DSP . It is possible that, with more owners and trainers reporting clinical signs, pain on palpation was not reported as frequently because owners and trainers are less likely than veterinarians to palpate the dorsum.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Few horses in the study population were reported to have pain on palpation of the dorsum. Hyperalgesia of the dorsum has been described as a clinical sign of thoracolumbar pain in the horse and has been documented in one report describing a study with experimentally induced pain of the DSP . It is possible that, with more owners and trainers reporting clinical signs, pain on palpation was not reported as frequently because owners and trainers are less likely than veterinarians to palpate the dorsum.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen horses met inclusion criteria, with a median age of 9 years (range, [3][4][5][6][7][8][9][10][11][12][13][14]. Breeds represented included seven warmbloods and warmblood crosses, seven thoroughbreds, two Irish sport horses, one draft cross breed, and one Appaloosa.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations